Oedipa Maas’s Struggle against Existential Nihilism in The Crying of Lot 49 - Moore, Samantha (Office of Student Research and Creative Activity, 2018)
This paper investigates the journey of protagonist Oedipa Maas in Thomas Pynchon’s novella The Crying of Lot 49, specifically through the lens of her resistance to existential nihilism. Her development throughout the novel provides the structure for this essay, which follows her as she numbs herself to avoid meaninglessness, sensitizes herself to fabricate meaning, becomes conscious of this fabrication, and collapses into and subsequently overcomes existential nihilism. Remedios Varo’s triptych, Bordando el manto terrestre, acts as an extended metaphor in this sense, highlighting Oedipa’s attempt to escape her symbolic tower and illuminate the void around her. The views of prominent existential philosophers and writers such as Nietzsche, Heidegger, and Kierkegaard also bring the book’s themes into focus. As Oedipa uses her newfound sensitivity to weave a world of countless connections and fantastic conspiracies, her arc follows her absurd quest to construct order in her world and thus avoid the anguishing existential nihilist crisis of facing meaninglessness or nonexistence.
Keywords: Nihilism (Philosophy) in literature; Existentialism in literature